Tunisia : Strengthening Early Childhood Development - World Bank (World Bank, Washington, DC, 2017)
As Tunisia emerges from the Arab Spring, its new constitution explicitly recognizes the rights of the child and the responsibility of both the State and parents to act in the child’s best interest to guarantee dignity, healthcare, protection, and education. In accordance with these guarantees, the Tunisian Ministry of Women, Family, and Childhood (MFFE) has utilized the Systems Approach for Better Education Results (SABER) diagnostic tools to analyze policies and programs that affect young children in Tunisia. Through this SABER-ECD collaboration with UNICEF and the World Bank, MFFE has used policy recommendations to develop its own multisectoral strategy to improve early childhood development (ECD) for Tunisia’s children.